Digital Innovation In Health Care: Review Article - Pratiksha Pund , Shweta A. Panchbudhe, Rakesh Kumar Jha , Shriram Kane (Drugs and Cell Therapies in Hematology, 2021)
Introducing how digital innovation in healthcare system has changed the lifestyle. The important goals of innovating the healthcare system digitally are to simplify physicians’ work, improving patient outcomes, reducing human error, and lowering costs through amazing web and mobile experiences. Innovation is the change made in an existing product or idea or field. It is the introduction of something new from the old one. In a number of nations around the world, digital health innovation is at the heart of attempts to modernize health care. Despite some evidence of influence on quality and efficiency, its implementation in practice has been described as a plague of pilots, with innovations failing to become standard practice because to a lack of money or the inability to expand to other parts of the health-care system. Despite the growing quantity of information about the elements that underpin success and failure, translating evidence into practice remains a difficulty. Conclusion: Digital innovation van take the heath care system to different level where patients can be treated conveniently. These findings and recommendations might be reflected on by health care systems and stakeholders around the world to examine their utility in furthering local health innovation agendas. Evaluations of digital health innovations should focus on understanding the characteristics that impact adoption of a specific innovation, in order to promote the development beyond the pilot stage to broader adoption, in order to support policy efforts.